A newly described group of thermal springs and solfatar fields on the western slope of Dokuchaev's ridge, Kunashir Island - Yuri N. Sundukov (Nature Conservation Research: Zapovednaâ Nauka, 2017)
As a result of field research in a remote and poorly studied area in the north-west of Kunashir Island, an unknown group of hydrothermal-solfataric post-volcanic activity was discovered on the western slope of the volcano Ruruy, named by the authors – Dal'nie springs. In total eight objects were examined: 1) two small solfataric fields, 2) a small lake and a small stream with «acid springs» and gas outlets, 3) two small glades with mofettes among the bamboo, on which a warm or fairly hot steam flows from small holes in the ground, 4) and two mountain lakes – Lake Vodopadnoe and Lake Khmuroe. Perhaps, the cup-like hollow in which the discovered objects are located is an ancient explosive crater formed on the western slope of volcano Ruruy as a result of a strong eruption.